Innovative Financing Models for Agricultural Waqf: A Conceptual Framework for Optimizing Resources and Investments - Kamal, Mustafa (ZISWAF, 2026)
This article aims to build an understanding of the emerging analytical discussions appearing in the research published on the topic of waqf in agriculture context. Employing a thematic analysis approach, this research synthesizes secondary data sourced from peer-reviewed articles across major academic databases (Scopus, Web of Science, and Google Scholar), alongside official institutional reports to identify key themes related to Islamic financial instruments, digital financing platforms, institutional governance, and sustainability orientation in agricultural waqf management. The analysis reveals that agricultural waqf can be transformed from a passive charitable asset into a productive development instrument through the integration of cash waqf, sukuk, Islamic financing contracts, fintech-based crowdfunding, and strengthened nazhir governance. Building on these findings, the study develops a conceptual framework based on the Tawhidi String Relations (TSR) approach, which emphasizes ethical unity, interconnectedness, and circular causation between economic activities, social welfare, and environmental sustainability. The proposed framework positions agricultural waqf as a strategic asset capable of addressing financing constraints, land fragmentation, and food security challenges while supporting the achievement of the Sustainable Development Goals (SDGs). This study contributes to the literature by offering a value-driven and integrative perspective on agricultural waqf financing and provides insights for policymakers, waqf institutions, and Islamic finance practitioners in designing sustainable and Shariah-compliant financing mechanisms.